How do demographic and socioeconomic factors affect financial literacy and its variables? - Vera Intanie Dewi (Cogent Business & Management, 2022)
The purpose of this study was to investigate various relationships between demographic and socioeconomic factors and financial literacy variables. Instead of using two or three variables as commonly adopted in the literature, this study employed multivariable analysis to investigate financial literacy. The sample of this research was 255 faculty members on Java Island, Indonesia. This study was a discrete moderator test; therefore, it employed a multigroup analysis (MGA) via the partial least squares of structural equations modeling (PLS-SEM) to determine which group of demographics and socioeconomic factors influencing the relationship of the financial literacy variables. This study revealed that demographic factors of sex, age, and specialization affected different relationship of financial skills, knowledge, capability, awareness, experience, goal, and financial decision. This study also provided empirical evidence that the socioeconomic factor of consumption spending affected the different relationships between financial awareness and skills. The results proved that demographic and socioeconomic factors enhanced financial literacy. Assessing financial literacy levels in different demographic and socioeconomic factors, as a key factor in accomplishing a successful national strategy for financial education, allows policymakers to identify gaps and design appropriate responses. This result emphasizes that strengthening awareness and experience as future orientations could improve financial literacy levels in developing countries.
Keywords: G23; G40; G53; 650; financial literacy; demographic; financial behavior; multigroup analysis